Anti–Melanoma Differentiation–Associated Gene 5 Is Associated With Rapidly Progressive Lung Disease and Poor Survival in US Patients With Amyopathic and Myopathic Dermatomyositis. Issue 5 (May 2016) - Moghadam‐Kia, Siamak; Oddis, Chester V.; Sato, Shinji; Kuwana, Masataka; Aggarwal, Rohit
Abstract : Objective: Clinically amyopathic dermatomyositis (CADM) is a subset of dermatomyositis (DM) presenting with the characteristic rash of DM without objective muscle weakness. Asian studies report that anti–melanoma differentiation–associated gene 5 (anti–MDA‐5) autoantibody in CADM is associated with interstitial lung disease (ILD), particularly rapidly progressive ILD (RPILD). These associations have not been established in US myositis patients. The goal of our study was to determine the association of anti–MDA‐5 autoantibody with ILD, RPILD, and survival in US patients with CADM and classic DM. Methods: CADM patients were identified in the University of Pittsburgh Myositis Center Database and matched 1:1 (sex and age) to classic DM controls. Anti–MDA‐5 was measured by serum enzyme‐linked immunosorbent assay. Kaplan‐Meier, log rank, and chi‐square tests were used for analysis. Results: We identified 61 CADM patients (62% women, mean age 48.2 years) and 61 classic DM controls (64% women, mean age 44.8 years). The frequencies of anti–MDA‐5 positivity, ILD, and RPILD were similar in the 2 cohorts (MDA‐5 positive: CADM 13.1% [8 of 61] and DM 13.1% [8 of 61], ILD positive: CADM 31.1% [19 of 61] and DM 26.2% [16 of 61], and RPILD positive: CADM 8.2% [5 of 61] and DM 5% [3 of 61]; P = 1, 0.55, and 0.46, respectively). Anti–MDA‐5 positivity was significantly associated with ILD, since 50% of MDA‐5–positive subjects (8 of 16) had ILD versus 25.5% of MDA‐5–negative subjects (27 of 106; P = 0.04). Anti–MDA‐5 was strongly associated with RPILD ( P < 0.001). Anti–MDA‐5–positive patients with ILD had worse baseline pulmonary function testing variables compared to anti–MDA‐5–negative patients. Anti–MDA‐5 positivity was significantly associated with poor survival ( P = 0.007). Conclusion: Anti–MDA‐5 antibody is significantly associated with ILD, RPILD, worse pulmonary outcome, and survival in US classic DM and CADM patients.